The macrofungi of Jammu and Kashmir- Russula species - Kumar, Sanjeev; Sharma, Yash Pal (Mushroom Research, 2012)
Five macrofungi were collected and identified as Russula annulata var. evanescens var. nov., R. cyanoxantha (Schaeff.)Â  Fr., R. lepida Fr., R. puellaris Fr. and R. tuberculosa R. Heim. These have been described and illustrated with photographs showing habit,, habitat, macro- and microscopic features. Russula annulata var. evanescens var. nov. has been proposed as a new variety while others are recorded for the first time in Jammu and Kashmir.